Exposure to Information Through E-Commerce Media and Its Influence on Product Purchasing Decisions - Mochammad Arifin; Totok Wahyu Abadi; Yasnaul Khakima; Sobirov Bobur Baxtishodovich; Anurat Anantanathorn (Communicatus: Jurnal Ilmu komunikasi, 2025)
Research purposes this is analyze and explain influence quality online transactions, trust, consumer behavior, information exposure, and e-commerce media to product purchase decision community in East Java. Research methods use approach quantitative with technique analysis path analysis of 205 respondents e-commerce platform users as sample. Research results show that influencing factors​ to product purchase decisions are e-commerce media (p = 0.001), information exposure (p = 0.009), and consumer behavior (p = 0.011). Temporary that, variable trust no influential direct to decision purchase (p = 0.785). Findings this show that experience users through e-commerce media, access digital information, and behavior consumer become factor main in the process of taking decision purchas.  Novelty study this lies in the findings that quality online transactions do not influential direct significant to decision purchase product and that risk online transactions instead own influence more big to interest buy, which emphasizes importance management risk in e-commerce practices. In addition, trust consumer play a role in a way no direct through complex and layered cognitive processes.​ Integration between​ behavior consumers and exposure information mediated by e-commerce media expands understanding about mechanism taking decision consumer through interaction various factor psychosocial and digital information . Implications strategic from study this recommend e-commerce companies for optimizing digital platforms, improving exposure information through communication interactive, and understanding behavior consumer data -based to improve effectiveness of communication strategies marketing in the digital economy era.